Implementasi Model Pembelajaran STAD Berbantuan Liveworksheets dan Dampaknya Terhadap Motivasi Berprestasi Siswa - Novitasari; Herianto, Edy; Kurniawansyah, Edy; M. Ismail (Jurnal Penelitian dan Pendidikan IPS, 2024)
This study aims to determine the impact of using the STAD learning model assisted by liveworksheets on achievement motivation to realize sustainable development goals (SDGs). This study uses a quantitative approach, the type is a quasi-experimental with a non-equivalent control group design. This study's population was all class XI MAN 2 Mataram students. The sample of this study was class XI IPS 1 and class XI IPS 3. The research instruments used were observation sheets and questionnaires. Analysis of hypothesis test data using paired sample t-test with a significance level of 5%. The results of the hypothesis test showed that the tcount> ttable (16,361> 2.037), so it can be concluded that Ha is accepted and Ho is rejected. This means that applying the STAD learning model assisted by liveworksheets affects students' achievement motivation to realize SDGs